2016
DOI: 10.15314/tjse.15230
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of atmosphere, satisfaction, and loyalty: Sample of a fitness center

Abstract: In the recent years, that fitness market rapidly grows, understanding of its importance and change of suggestions according to demand also revealed the importance of intangible elements as well as tangible elements. The aim of this study is to measure the relationship of atmosphere, satisfaction, and loyalty the customers, who are member to a private fitness center, perceive from this center. The study group consists of 503 participants (nmale = 465; nfemale = 38), who are at least for six month to a private f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…The sellers cannot be stagnant at one point but require feedback from customers (in this regard it is hope). This study is in line with what was found by many previous researchers who concluded that store atmosphere indirectly has a significant impact on customer satisfaction with the help of SERVQUAL (Oztas et al, 2016;Mensah, Mensah, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The sellers cannot be stagnant at one point but require feedback from customers (in this regard it is hope). This study is in line with what was found by many previous researchers who concluded that store atmosphere indirectly has a significant impact on customer satisfaction with the help of SERVQUAL (Oztas et al, 2016;Mensah, Mensah, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The result is also significant at 0.05 level of significance (p < 0.05). The result is consistent with the work of Oztas et al (2016). They conducted a study called "The Relationship of Atmosphere, Satisfaction, and Loyalty: Sample of a Fitness Center. "…”
Section: Theoretical Implicationsupporting
confidence: 86%
“…pleasure and arousal) as an organism mediating variable in stimulus-organism-response framework. In line with this, many scholars have clearly reported on a mediating influence for customer emotions on the relationship between ambient conditions and customer behavioral responses (Baker et al, 1992;Chang et al 2014;Foroughiet al, 2019;Oztas et al, 2016;Walsh et al, 2011). Ambient factors were concluded to positively affect customer positive emotions, which in turn drive customer impulse buying behavior (Chang et al, 2014).…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 87%
“…Likewise, Quartier et al (2014) noted that intangible factors such as lighting can have hidden effects on customer emotions, thus, can be utilized to deliver a certain image. Oztas et al, (2016) reported that fitness center lighting and temperature levels can influence customer emotions more than paintings and pictures. In the same venue, Bilgili et al, (2018) founded that cool lighting (e.g.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation